Preserving fertility in women with cancer (PreFer): Decision‐making and patient‐reported outcomes in women offered egg and embryo freezing prior to cancer treatment. Issue 12 (10th October 2018) - Vogt, Katharina S.; Hughes, Jane; Wilkinson, Anna; Mahmoodi, Neda; Skull, Jonathan; Wood, Hilary; McDougall, Sophia; Slade, Pauline; Greenfield, Diana M.; Pacey, Allan; Ledger, William; Jones, Georgina L.
Abstract: Objective: Women of childbearing age with new cancer diagnoses have to make rapid decisions about fertility preservation (FP) before starting cancer treatment (CT). The aim of the PreFer study was to explore this FP decision‐making process and its impact on patient‐reported outcomes (PROMs) and health‐related quality of life (HRQoL). Methods: A prospective, mixed‐methods design was used (questionnaires, in‐depth interviews). Interviews were analysed using thematic analysis. Fifty‐eight women with new cancer diagnoses were recruited. Comparisons were made between women who declined FP referral in oncology (Group1) and women who chose referral (Group2). Group 2 was further split into those who had some FP (2A) and those who did not (2B). Questionnaires and PROMs were administered prior to and after the fertility consultation, before the start of CT and 3 months post CT. Interviews were conducted with one participant from Group 2. Results: HRQoL was negatively affected, particularly depression. Women's lack of understanding about the relationship between CT and fertility were evident. Five themes emerged from the interviews as barriers and facilitators to the FP decision‐making process. Conclusion: The results indicate that better information and support resources aimed at women to support their decision making are needed, such as patient decision‐aids. Women from Group 1 were found to suffer significantly worse depression compared with the general UK population, highlighting the need for psychological support in the FP care‐pathway and for research exploring the contributions of depression and hopelessness to the decision‐making process.